INFECTIOUS DISEASES AND THE BRAZILIAN POPULATION DEPRIVED OF FREEDOM - Carvalho, Rosania Lemes de; Silva Matias, Paulienne Ramos da; Pereira, Jéssica Rodrigues; Oliveira, Letycia Parreira de (Cadernos ESP, 2022)
To describe through an integrative review of the literature the phenomenon of infectious diseases among individuals deprived of liberty in the Brazilian prison system. This is an integrative review of the literature that observes the concerns of the investigated area by adding the nursing practices, in which it was consulted through the databases of the VHL (Virtual Health Library) LILACS, MEDLINE, SciELO and BDENF. We selected 14 publications that gave rise to three categories: Main infectious diseases affected in the Population Deprived of Liberty, Relationship of the environment with co-infections and The role of nursing in the face of the reality of prison. It is understood that scientific production points to a precarious Brazilian prison system, which ends up facilitating the transmission of infectious diseases among PPL, and for this reality to be changed, it is urgent to take action against the control of these diseases, based on current public policies, so that there is a positive result.